“I Know Why the Caged Bird Sings”: An Illustration of Patriarchal Oppression - Sheikh, Asmat A.; Suleman, Nazia; Ali, Hira; Asghar, Tahira; Rahim, Sadia; Munir, Haniya (Revista de la Universidad del Zulia, 2020)
This paper aims to examine the issues of sexual violence, sexual abuse, sexual exploitation and sexual politics in the text of ‘I Know Why the Caged Bird Sings’ by Angelou (1969). And all these issues signal towards the major issue of female exploitation at the hands of patriarchy. The proposed study is qualitative in nature and uses framework of the great black feminist writer Collins (2004) which gives a clear insight into the male psychology exposing us how men make themselves superior by suppressing and repressing the identities of women and by exploiting them sexually. Collins (2004) is of the view that female exploitation has been used as the basic ingredient in the formation of masculinity of males. The findings of the study indicate that the various experiences of women throughout the selected text helped unveil the ways of patriarchal oppression, female exploitation and sexual harassment at the hands of patriarchy through the miserable condition of the character of ‘Maya’ who suffers at the hands of black man who continuously exploits her in order to fulfill his evil deeds. The findings also reveal that the after-effects of patriarchal oppression and sexual harassment lead the black women towards the rebellion against these obnoxious crimes. This study will go a long way in helping black women in their efforts and attempts to eradicate the evil crime of sexual harassment done by the men of their own communities. Moreover, applying the same frameworks, other texts produced by the same or other Black writers can also be investigated by the future researchers.